Serum adiponectin level in obstructive sleep apnea: Relation of adiponectin to obesity and long-term continuous positive airway pressure therapy - Hobzová, Milada; Salzman, Richard; Stejskal, David; Zapletalová, Jana; Kolek, Vítězslav (Advances in medical sciences, 2016)
PURPOSE: The study aimed to determine the effect of OSA and obesity on the plasma levels of adiponectin and the long-term effect of CPAP on its plasma levels and obesity parameters. MATERIAL/METHODS: A prospective observational study included 159 newly diagnosed OSA patients. The cohort was divided into CPAP treated (n=82) and control group (n=77). Both groups were examined at the beginning and a year later. The CPAP-treated patients were additionally tested after a month of therapy. The examinations included Epworth Sleepiness Scale questionnaire, anthropometric and polysomnographic measurements, and blood serum tests. Changes in the studied parameters of OSA, obesity, and adiponectin obtained at the beginning and after follow-up period were compared in each group. RESULTS: In CPAP group, all studied OSA parameters improved already after a month of CPAP therapy. Contrarily, obesity parameters (except of neck and waist circumference) remained unchanged after CPAP therapy. Serum adiponectin levels dropped during CPAP therapy. In the control group, both obesity and OSA parameters did not show changes. The only exceptions were deteriorated mean SpO2 and decreased hip circumference. Adiponectin remained unchanged in this group. In neither group, the Spearman correlation analyses showed any association of serum adiponectin levels with obesity or OSA parameters, except of mean SpO2. CONCLUSIONS: Only correlation found was between adiponectin and mean SpO2. Although CPAP therapy improves all OSA parameters, it did not change most obesity parameters. Additionally in the CPAP group, there was a significant drop in adiponectin levels, suggesting its protective role in this group of patients.
Keywords: demografie; Young Adult; adiponektin; Male; kohortové studie; Obesity; mladý dospělý; Cohort Studies; Demography; Adolescent; obstrukční spánková apnoe; obezita; Adult; Aged; dospělí; Sleep Apnea, Obstructive; mužské pohlaví; senioři; Continuous Positive Airway Pressure; mladiství; lidé; ženské pohlaví; Humans; trvalý přetlak v dýchacích cestách; Adiponectin; Female; lidé středního věku; Middle Aged